Fossil Alloceltidoxylon, Allonymphaea, Arecocaryon, Paralnoxylon and Paranyssa and extant Komaroviopsis, Marcanodendron, and Papyrocactus (Magnoliophyta), new replacement generic names - Doweld, Alexander B. (Phytotaxa, 2021)
Eight new generic replacement names were validated. The new fossil wood generic name Alloceltidoxylon is validated to replace later homonym, Scottoxylon Wheeler & Manchester (non Scotoxylon Vogellehner). The new fossil generic name Allonymphaea is proposed to replace later homonym, Thiebaudia M. Chandler (non Thiebautia Colla nec Thibaudia Ruiz et Pavon ex Jaume St.-Hilaire), based on leaf remains. The new fossil generic name Arecocaryon, based on fruit remains, is proposed to replace the later homonym Friedemannia M.E. Collinson, Manchester& V. Wilde (non Friedmannia Chantanachat & Bold, Algae). The new fossil wood generic name Paralnoxylon is validated to replace later homonym, Cantia Stopes (non Kantia Pia). The new fossil generic name Paranyssa, based on fossil leaves, is validated to replace later homonym, Browniea Manchester & Hickey (non Brownea Jacquin). Three new generic names for extant flowering plants were validated: Komaroviopsis replaces Komarovia Korovin (non Komaroffia O. Kuntze) and Komaroviopsideae trib. nov. replaced invalid Komarovieae, Marcanodendron instead of Uladendron Marcano-Berti (non fossil Ulodendron Lindley & Hutton) and Papyrocactus replaces Toumeya Britton & Rose (non Tuomeya W.H. Harvey, Algae). The new combinations Alloceltidoxylon eocenicum, Allonymphaea rayaniensis, Arecocaryon messelense, Paralnoxylon arborescens, Paranyssa serrata, Komaroviopsis anisosperma, Marcanodendron codesuri, and Papyrocactus papyracanthus are proposed. Alloceltidoxylon, Allonymphaea, Arecocaryon, Komaroviopsis, Marcanodendron, Paralnoxylon, Paranyssa, Papyrocactus, new replacement generic names, Komaroviopsideae trib. nov.